Linking Pathways from Perceived Absolute Risk and Social Support to Female Regular Health Screening: Integrated with Social Cognitive Theory Model (The Journal of Medicine, Humanity and Media, 2025)
The increasing incidence of cancer among women of childbearing age has emerged as a significant health crisis, necessitating urgent attention from both individuals and societal medical systems. Cancer-related screening and prevention strategies are prevalent public health responses to this challenge. This study integrates the Social Cognitive Theory (SCT) with the Health Belief Model (HBM) and Self-Determination Theory (SDT) to examine the psychological and behavioral factors influencing health outcomes. Specifically, it investigates how perceived absolute risk, self-efficacy, self-regulation, social support, and health screening behaviors interrelate, focusing on their mutual reinforcement in the context of female health regulation. Addressing a gap in existing research on health behavior change in a sustainable loop, this study employs a nationally representative online survey with 904 female participants. Data were analyzed using Structural Equation Modeling (SEM), revealing that the integrated model exhibited a good fit and that all five hypotheses were supported. The findings emphasizing the importance of psychological and behavioral impacts on public health behaviors.
Keywords: Social Cognitive Theory; perceived absolute risk; self-efficacy; self-regulation; social support; female health regular screening